Structural basis for GPR40 allosteric agonism and incretin stimulation - Joseph D. Ho (Nature Portfolio, 2018)
GPR40 is a G-protein coupled receptor that binds to free fatty acids, mediating insulin and incretin secretion. Here, the authors present the crystal structure of human GPR40 with an agonist bound to an allosteric site located near the lipid-rich region that suggests a mechanism for biased agonism.